Stability of Linear Delay Differential Equations using Modified Algebraic Approach - Mohammedali, K. H.; Ahmad, N. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
An algebraic approach have been developed to study the stability of delay differential equations with m-retarded arguments, each of them is a multiple of fixed unknown time lag. The method has its basis upon transforming the characteristic equation related to the delay differential equation into an equivalent system of two algebraic equations in order to evaluate the value of the time lag which ensures the stability of the delay differential equation.